2011
DOI: 10.1007/s11090-011-9309-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Microcystis aeruginosa with Contact Glow Discharge Electrolysis

Abstract: This work investigated the inactivation of Microcystis aeruginosa (MA) with contact glow discharge electrolysis (CGDE). The influences of applied voltage, current and treatment time on the inactivation rate were critically examined. Based on the above results, the optimal conditions were chosen to sufficiently utilize chemically active species and enhance the inactivation of MA. Under the optimal conditions (voltage: 530 V; current: 30 mA; treatment time: 20 min), the inactivation rate of algae was more than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Besides the energetic particles including negatively charged electrons and positively charged ions, the accompanying intrinsic UV emission and impact waves, chemically active substances such as hydrogen, oxygen, hydrogen peroxide and active radicals such as hydroxyl radical, hydroperoxyl radical, oxygen radical and hydrogen radical are produced during the plasma discharge 2 25 26 27 28 . These active chemical species can inactivate algal cells as reported by our previous study 2 and other studies 1 12 15 .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Besides the energetic particles including negatively charged electrons and positively charged ions, the accompanying intrinsic UV emission and impact waves, chemically active substances such as hydrogen, oxygen, hydrogen peroxide and active radicals such as hydroxyl radical, hydroperoxyl radical, oxygen radical and hydrogen radical are produced during the plasma discharge 2 25 26 27 28 . These active chemical species can inactivate algal cells as reported by our previous study 2 and other studies 1 12 15 .…”
supporting
confidence: 71%
“…Therefore, there is an urgent need to develop efficient techniques to control and reduce the adverse impact of blooms. To suppress or remove cyanobacteria blooms, various methods have been adopted such as chemical treatment 3 4 5 , UV radiation 6 7 , ultrasound irradiation 8 9 10 , electron beam irradiation 11 and non-thermal plasma oxidation technology 2 12 13 14 15 16 . However, the chemical methods such as excessive use of algaecides can lead to secondary pollution, while the physical methods such as UV radiation, sonication and electron-beam irradiation have the limitation for bloom control with high efficiency or on a large scale.…”
mentioning
confidence: 99%
“…It was reported that this type of plasma sources was applied so far to the purification of water from organic dyes [8][9][10][11], phenol [12][13][14], or organic halides [15][16][17] and to the sterilization of water [1,18] and its bio-decontamination [19][20][21]. The discoloration of wastewaters containing various dyes and the decomposition of other organic compounds by glow discharges (GDs) were rather frequently studied in various plasma reactors and electrode configurations, i.e., discharges in liquids termed as glow discharge electrolysis (GDE) [10,16], discharges in contact with liquids termed as contact glow discharge electrolysis (CGDE) [6,9,12,[20][21][22][23] and discharges between two liquids separated by thin diaphragm holes termed as diaphragm glow discharge (DGD) [11,17]. It was also possible to inactivate glutathione [20], cyanotoxins (microcystin-LR) [21] or cyanobacteria (microcystis aeruginosa) in fresh waters by CGDEs [22].…”
Section: Introductionmentioning
confidence: 99%
“…The discoloration of wastewaters containing various dyes and the decomposition of other organic compounds by glow discharges (GDs) were rather frequently studied in various plasma reactors and electrode configurations, i.e., discharges in liquids termed as glow discharge electrolysis (GDE) [10,16], discharges in contact with liquids termed as contact glow discharge electrolysis (CGDE) [6,9,12,[20][21][22][23] and discharges between two liquids separated by thin diaphragm holes termed as diaphragm glow discharge (DGD) [11,17]. It was also possible to inactivate glutathione [20], cyanotoxins (microcystin-LR) [21] or cyanobacteria (microcystis aeruginosa) in fresh waters by CGDEs [22]. The removal of inorganic hazardous chemicals from waters by APGDs was faintly examined.…”
Section: Introductionmentioning
confidence: 99%
“…These highly energetic electrons produce free radicals from parent molecules in multi-step physical and chemical processes, leading to high destructive ability [1][2][3][4][5][6][7] . In terms of treating wastewater, NTP has been utilized in several studies to degrade organic pollutants [8][9][10][11][12][13][14][15] , to inactivate algae [16] and to reduce chromium VI [17][18] . Different categories of glow discharge plasmas were generated in abovementioned studies and utilized for treating wastewater such as direct glow discharge, diaphragm glow discharge and anodic and multi anode contact glow discharge electrolysis.…”
Section: Introductionmentioning
confidence: 99%